1992
DOI: 10.1007/bf00122574
|View full text |Cite
|
Sign up to set email alerts
|

Advances in prospect theory: Cumulative representation of uncertainty

Abstract: We develop a new version of prospect theory that employs cumulative rather than separable decision weights and extends the theory in several respects. This version, called cumulative prospect theory, applies to uncertain as well as to risky prospects with any number of outcomes, and it allows different weighting functions for gains and for losses. Two principles, diminishing sensitivity and loss aversion, are invoked to explain the characteristic curvature of the value function and the weighting functions. A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

130
3,158
22
50

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11,639 publications
(3,879 citation statements)
references
References 37 publications
130
3,158
22
50
Order By: Relevance
“…Arguably the most influential descriptive model in the expectation tradition is cumulative prospect theory (CPT, Kahneman & Tversky, 1979;Tversky & Kahneman, 1992).…”
Section: Prospect Theory Reflects Selective Allocation Of Attentionmentioning
confidence: 99%
“…Arguably the most influential descriptive model in the expectation tradition is cumulative prospect theory (CPT, Kahneman & Tversky, 1979;Tversky & Kahneman, 1992).…”
Section: Prospect Theory Reflects Selective Allocation Of Attentionmentioning
confidence: 99%
“…A first potential aspect that may provide a welfare gain to insured when taking out SHI is loss aversion, which is a key insight from the 'cumulative prospect theory' developed by Tversky and Kahneman [18]. Loss aversion regards the phenomenon that 'losses loom larger than gains' and that 'the aggravation that one experiences in losing a sum of money appears to be greater than the pleasure associated with gaining the same amount' [11].…”
Section: Loss Aversionmentioning
confidence: 99%
“…Studies based on real data show that such rationality can be rarely observed; instead, decision-making in a wide range of situations systematically deviates from fundamental rationality postulate (Allais 1953, Ellsberg 1961, Kahneman and Tversky 1979, Tversky and Kahneman 1992.…”
Section: Introductionmentioning
confidence: 97%
“…4 The application of prospect theory allows us to depict investor behavior and risk-taking more accurately than rationality-based expected utility theory by accounting for behavioral aspects Tversky 1979, Tversky andKahneman 1992). Based on this theory, loss offset restrictions interact with the psychological imbalance of investors assigning more weight to a loss than to a correspondingly large gain.…”
Section: Introductionmentioning
confidence: 99%